EKSPLORASI PENGGUNAAN MEDIA PEMBELAJARAN LIQUID CRYSTAL DISPLAY PROJECTOR DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DISEKOLAH MENENGAH PERTAMA NEGERI 10 MERANGIN - Imro'atul, Ella; Jaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the use of Liquid Crystal Display (LCD) projector learning media in increasing students’ learning motivation in Islamic Religious Education and Character Education subjects at State Junior High School 10 Merangin. The main problem of this study is the low level of students’ participation, attention, and seriousness during the learning process, which indicates the need for more innovative and engaging learning media. This research employed a qualitative approach using field research design. Data were collected through classroom observation, in-depth interviews with Islamic Religious Education teachers and students of class VIII B, and documentation. The data were analyzed descriptively through data reduction, data display, and conclusion drawing in order to obtain a comprehensive understanding of the implementation of LCD projector-based learning. The findings reveal that the use of LCD projectors through videos, PowerPoint presentations, and visual images increases students’ interest, attention, and learning focus. Visual and audiovisual presentations make the learning process more engaging, interactive, and less monotonous, thus helping students to understand learning materials more easily. Students showed higher enthusiasm, were more active in classroom discussions, and demonstrated stronger motivation to participate in learning activities. Supporting factors include the availability of facilities, teachers’ competence, and school support, while inhibiting factors consist of electricity interruptions, inadequate classroom lighting, and limited equipment. Overall, the use of LCD projectors has a positive impact on students’ learning motivation, although several technical constraints still need to be addressed